Treating alcohol problems - Rotgers, Frederick (Wiley, 2006)
Part of the Wiley Series on Treating Addictions, Treating Alcohol Problems offers the latest evidence-based guidance on effectively diagnosing and treating the full spectrum of problems related to drinking. Whether you are an addictions counselor, mental health professional, or physician, you can use this all-in-one guide as a stepping-stone to seek out and develop better treatment options for your clients.